A review of the theory and practice of regional resilience. (February 2017) - Peng, Chong; Yuan, Minhang; Gu, Chaolin; Peng, Zhongren; Ming, Tingzhen
Highlights: The concepts of resilience and regional resilience were summarized. The definition, research background, visual angle of regional resilience were analyzed. The basic research framework and future development of regional resilience were analyzed. The predominant methods and technologies were summarized to evaluate regional resilience. Abstract: The concept of resilience deeply affects regional planning, development, and post-disaster reconstruction. Recent research advances on the theories and practices of regional resilience are discussed in this article. First, the concepts of resilience and regional resilience are summarized, and the spatial characteristics of the resilient region are analyzed from the standpoints of property, process and capability. Second, the definition, research background, visual angle, basic research framework, guidelines, importance, and future development of regional resilience are evaluated from the following point of views: engineering, economy, ecology, and society. In addition, the predominant methods and technologies are reviewed to evaluate the regional resilience from the perspectives of property, process and capability factors. This is followed by a detailed discussion on the practice of regional resilience in planning and disaster management. Last, but not least, the worldwide main research results, their current deficiencies, and future research directions are presented.